Modernisasi Pendidikan Islam Pesantren Dalam Tinjauan Filosofis Metodologis - Indhra Musthofa (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2019)
Abstract The development of pesantren is very interesting to be discussed. This is because the boarding school is an Islamic educational institution of Indonesia that is believed to be able to mint the student who are characterized and become the guidance of society in religious life. Pesantren in its development follow the development of the times that always move to a better direction, so there are some values and systems that are renewed. This review will discuss the change of pesantren towards the modernization of Islamic education in philosophical methodological review. In this study there is a discussion of modernization in terms of historical aspects and their understanding from various opinions of experts. Modernization that occurs in Islamic educational institutions has an impact on Islamic educational institutions, thus giving birth to the pattern of modernization and modernization form. Motivation in pesantren learning also develops in order to upgrade students ability and adjustment of time.